Maternal influence on the fetal microbiome in a population-based study of the first-pass meconium. (September 2018) - Tapiainen, Terhi; Paalanne, Niko; Tejesvi, Mysore; Koivusaari, Pirjo; Korpela, Katja; Pokka, Tytti; Salo, Jarmo; Kaukola, Tuula; Pirttilä, Anna Maria; Uhari, Matti; Renko, Marjo
Abstract Background Meconium is formed before birth and may reflect the microbiome of the fetus. To test our hypothesis, we investigated whether maternal factors during pregnancy, such as biodiversity of the living environment, influence the microbiome of the first stool more than immediate perinatal factors. Methods We recruited 218 consecutive newborn infants from one hospital. Regions of the bacterial 16S rRNA gene were sequenced to characterize the microbiomes of the first-pass meconium samples (N =212). We used a multivariate model to determine both the prenatal and perinatal factors affecting the microbiome. Results The number of operational taxonomic units ranged from 0 to 448 per newborn. The most abundant phyla were Firmicutes, with a relative abundance of 44%, Proteobacteria, 28%, and Bacteroidetes, 15%. By a multivariate analysis, the biodiversity of the home environment increased the diversity of microbiomes, whereas perinatal factors, such as the delivery mode or exposure to antimicrobials during labor did not have an effect. Conclusion The microbiome of the first-pass meconium was not altered by immediate perinatal factors, but was affected by maternal factors during pregnancy, implying thein utero transfer of microbes and the development of the gut microbiota niche in fetal life.